Taṭwīr Mawād Ta’līm Mahārah al-Kalām ‘ala Asās al-Anṡrūbūlūjiyā bi Jāmi’ah Maulānā Mālik Ibrāhῑm al-Isl āmiyyah al-Ḥukūmiyyah Malang - Nur Hasaniyah; Murdiono Murdiono; Suharmon Suharmon (IAIN Salatiga, 2021)
This study aimed to develop speaking skills teaching materials for anthropology-based tourism in the Arabic Language and Literature Department, Maulana Malik Ibrahim State Islamic University Malang; This study used Research and Development adapted from the Borg and Gall development model. The data were collected using the following instruments: interviews, participatory observation, questionnaires, and tests. The techniques of data analysis included qualitative and statistical descriptive. The results of this study were the availability of speaking skills teaching materials developed for anthropology based tourism in the Arabic Language and Literature Department, Maulana Malik Ibrahim State Islamic University Malang in the form of a textbook, entitled: “Al Arabiyyah li As Siyaahah: Ta`lim Maharah Al Kalam li As Siyaahah ála Asas Antropologi.” This textbook consists of 3 main sections: introduction, learning materials, and closing; As for the opinion of students, this product is good because it can contribute to increasing student enthusiasm and learning outcomes; and the T-test with SPSS shows that the average score of students on the posttest was higher than the pretest and statistically shows a significant increase.